Acoustic Estimation of Resonance Frequency and Sonodestruction of SonoVue Microbubbles - JURKONIS, Rytis; LAMANAUSKAS, Nerijus; SATKAUSKAS, Saulius (Archives of Acoustics, 2015)
Acoustic properties of ultrasound (US) contrast agent microbubbles (MB) highly influence sonoporation efficiency and intracellular drug and gene delivery. In this study we propose an acoustic method to monitor passive and excited MBs in a real time. MB monitoring system consisted of two separate transducers. The first transducer delivered over an interval of 1 s US pulses (1 MHz, 1% duty cycle, 100 Hz repetition frequency) with stepwise increased peak negative pressure (PNP), while the second one continuously monitored acoustic response of SonoVue MBs. Pulse echo signals were processed according to the substitution method to calculate attenuation coefficient spectra and loss of amplitude. During US exposure at 50–100 kPa PNP we observed a temporal increase in loss of amplitude which coincided with the US delivery. Transient increase in loss of amplitude vanished at higher PNP values. At higher PNP values loss of amplitude decreased during the US exposure indicating MB sonodestruction. Analysis of transient attenuation spectra revealed that attenuation coefficient was maximal at 1.5 MHz frequency which is consistent with resonance frequency of SonoVue MB. The method allows evaluation of the of resonance frequency of MB, onset and kinetics of MB sonodestruction.